Terlipressin for septic shock patients: protocol for a systematic review and meta-analysis - Zhu, Yibing; Huang, Huibin; Wang, Yang; Zhang, Linlin; Xi, Xiuming; Du, Bin (Journal of Emergency and Critical Care Medicine, 2018)
Background: Catecholamines are commonly used inseptic shock but face limitations of their hypo-responsiveness and adverseevents (AEs) due to high dose. Vasopressin and its analogs have been used forrescue agents in the septic shock. Terlipressin, a synthetic analog ofvasopressin, with its similar pharmacodynamic profile but greater selectivityof V1 receptor, is a potentially potent substitute in vasopressor therapy.Thus, we aim to conduct a meta-analysis to further investigate the efficacy andsafety of terlipressin for septic shock. Methods: Three electronic data sources (Embase,PubMed and Cochrane library) will be searched. Randomized controlled trials(RCTs) evaluating terlipressin in comparison with catecholamines in septicshock patients will be included. Outcome measures are mortality, length of stayin intensive care unit (ICU-LOS), duration of mechanical ventilation (MV),catecholamines requirement, and AEs. Subgroup and sensitivity analyses will beused to add robustness of the primary outcome. PROSPERO registration number: CRD42018104924.